Male obesity and semen quality: Any association? - Obose Rufus; Osaikhuwuomwan James; Aziken Michael (Shahid Sadoughi University of Medical Sciences, 2018)
Abstract Background: Infertility as well as obesity are risng global concern. Whilst there is an established association between female obesity and infertility, a similar link is yet to be proven in men. Objective: To determine the effects of elevated body mass index (BMI) on semen quality among male partners of infertile couples attending an infertility clinic. Materials and Methods: In this cross-sectional study, 206 men who met the inclusion criteria were recruited for the study. Selected participants were grouped according to their BMI (kg/m2): normal BMI (18.5-24.9 kg/m2) and elevated BMI (≥25 kg/m2). The effect of weight on semen quality was assessed based on sperm count, percentage motility, and morphology. Results: The number of participants with normal BMI was 110 (53.4%) while those with elevated BMI were 96 (46.6%). Of the participants in elevated BMI group, 52 (25.2%) were overweight and 44 (21.4%) were obese. There was no statistically significant difference in the semen quality as well as the pattern of semen parameter abnormalities between males with normal and elevated BMI (overweight or obese) (p=0.813). Conclusion: Elevated BMI did not significantly influence semen quality.